Global Resolvability for Quasilinear Hyperbolic Systems (Journal of Partial Differential Equations, 1995)
In this paper, we consider the globally smooth solutions of diagonalizable systems consisted of n-equations. We give a sufficient condition which guarantees the global existence of smooth solutions. Tb.e techniques used in this paper can be applied to study the globally smooth (or continuous) solutions diagonalizable noostrict hyperbolic conversation laws.
Keywords: Global resolvability; maximum principle; function transformation